Bio-TIM - Ambiente para convergência de informações em Bioinformática - Oliveira, Gustavo Borges de (2005)
Currently, some genomas of creatures are being mapping, so enormous amounts of data are being generated. This data is sometimes stored in different data sources and at many times, these sources are heterogeneous and distributed, which results in the necessity of the use of new query techniques and integration of data. After this, the biologists can usufruct greaters and better resources during the research process. This work has the proposal of to build a Bioinformatics environment for the integration of different data sources and their reorganization in a centered source that supports a flexible and efficient manner to build queries. The environment is called as Bio-TIM, which is composed by three layers. The main one is called "Mediator" and it is composed by a connection manager for databases management systems, by wrappers, by a Data Warehouse and by a specific database.